Epidemiological Study for Evaluation of Etiology and Risk Factors in Patients with Low Back Pain. (May 2014) - Krishna, V. Komuravalli; Sharma, D.; Samuel, G.
Introduction: To study the epidemiology, etiology and risk factors among patients with low back pain. In addition, it includes evaluation of efficacy of protocol suggested by American College of Physician (ACP) and American Pain Society (APS) 2007 in Indian population. Finally, to develop a possible protocol for India, in managing patients with low back pain. Materials and Methods: Epidemiology of patients with low back pain which includes demographic variables such as age, gender, education, occupational history, body mass index (BMI), diet habits, smoking, alcohol intake, comorbid conditions, life style factors, family history, and finally psychosociological factors by fear avoidance Belief Questionnaire (FABQ) were recorded. Focused history, examination, stratification, and further evaluation were done in accordance with protocol as suggested by ACP/APS 2007. Each patient was followed up monthly for 6 months to assess the outcome of stratification and treatment modalities advised. However, apart from pharmacological therapy, exercise therapy alone was used in both acute and chronic cases. Transition among stratified groups was evaluated. Results: Category Surgical intervention (%) Lost follow-up (%) Recurrence (%) Nonspecific back pain 0 4.9 12.4 Low back pain with radiculopathy 97.5 6.7 12.7 Back pain due to specific cause 2.5 2 0 Total number of patients evaluated were 506. Mean age of presentation was 41.15 ± 11.21 years in females and 39.13 ± 12.76 years in males. Most common age group involved were 36 to 40 years. Gender distribution shows that females were 52.6% and males were 47.4%. Literates were 68.4%. Occupation involving prolonged sitting account for majority of cases with 45.3%. Prolonged static posture such as sitting at work period, bending, and lifting activities were significantly ( p < 0.05) associated with low back pain. However, no association was found with BMI, diet habits, smoking, life style factors. Mean FABQ score was more among chronic group compared with acute group but scores in patients with progression from acute to chronic were not significant. Etiology includes nonspecific back pain in 51.9%, intervertebral disc prolapse in 23.1%, spondylolisthesis in 10.4%, spinal canal stenosis in 4.7%, osteoporotic fractures in 3.7%, tuberculosis and inflammatory spondyloarthritis in 2.1% each, tumor conditions account for 1.3%, and finally 0.1% pyogenic discitis. Total 82.6% among category I, 100% of category II, 95.3% among category III were correctly identified based on approach used by protocol. However, the transition among categories was significant; 5.3% were lost to follow-up. Outcome analysis shows that 88.7% were symptom free and 11.3% had recurrence rate at the end of 6 months. Conclusion: Low back pain continues to be an enormous social, psychological and financial problem with many speculated risk factors with none being convincible till time. From the present study, epidemiological profile of Indian population was depicted. Etiological diagnosis in low back pain patients still includes nonspecific back pain, a leading cause with 51.9%. However, it is a diagnosis of exclusion. Risk factor analysis shows that prolonged static postures at work place, activities involving bending and lifting were found to be statistically significant. In addition, using FABQ in assessment of psychosocial factors in low back pain is necessary and helpful in managing patients. However, the efficacy needs to be further evaluated. Regarding the evaluation of guidelines and its applicability, it is not advisable to use in Indian population. However, it forms a blueprint on which modifications such as investigating to rule out tuberculosis and spondylolisthesis in Indian population will be helpful before labeling any case as nonspecific back pain. Disclosure of Interest None declared References Solomen L, Warwide D, Nayagam S. Apley's System of Orthopedics and Fractures. 9th ed. London, UK: Hodder Arnold Publication; 2010:974 Secer M, Nacar OA, Muradov MJ, et al. Nonspecific low back pain in a group of young adult men. Turk Neurosurg 2011;21(2):135–139 Chou R, Qaseem A, Snow V, et al; Clinical Efficacy Assessment Subcommittee of the American College of Physicians; American College of Physicians; American Pain Society Low Back Pain Guidelines Panel. Diagnosis and treatment of low back pain: a joint clinical practice guideline from the American College of Physicians and the American Pain Society. Ann Intern Med 2007;147(7):478–491 Sharma SC, Singh R, Sharma AK, Mittal R. Incidence of low back pain in workage adults in rural North India. Indian J Med Sci 2003;57(4):145–147 Hult L. Cervical, dorsal and lumbar spinal syndromes; a field investigation of a non-selected material of 1200 workers in different occupations with special reference to disc degeneration and so-called muscular rheumatism. Acta Orthop Scand Suppl 1954;17:1–102 Nachemson AI. The lumber spine, an orthopaedic challenge. Spine 1976;11:59–71 Borenstein DG. A clinician's approach to acute low back pain. Am J Med 1997;102(Suppl 1A):16S-22S Deyo RA, Rainville J, Kent DL. What can the history and physical examination tell us about low back pain? JAMA 1992;268(6):760–765 Deyo RA, Bass JE. Lifestyle and low-back pain. The influence of smoking and obesity. Spine 1989;14(5):501–506 Jones GT, Johnson RE, Wiles NJ, et al. Predicting persistent disabling low back pain in general practice: a prospective cohort study. Br J Gen Pract 2006;56(526):334–341